The benefits of modified FOLFIRINOX for advanced pancreatic cancer and its induced adverse events: a systematic review and meta-analysis - Hongxuan Tong (Nature Portfolio, 2018)
Abstract FOLFIRINOX has been one of the first-line options for advanced pancreatic cancer, even though it induces significant adverse effects. Several institutions have begun using modified FOLFIRINOX to decrease its side effects and increase its tolerability. We systematically investigated the outcome from patients who initially received modified FOLFIRINOX as a chemotherapy regimen for advanced pancreatic cancer. We used the random-model generic inverse variance method to analyse the binary data with 95% confidence intervals (CIs). Eleven studies were included in the meta-analysis with 563 total patients. The 6-month and 1-year overall survival (OS) rates of locally advanced pancreatic cancer (LAPC) were 90.9% and 76.2%. The 6-month and 1-year progression-free survival (PFS) rates of LAPC were 81.5% and 48.5%. The 6-month and 1-year OS rates of metastatic pancreatic cancer (MPC) were 79.7% and 47.6%. The 6-month and 1-year PFS rates of MPC were 56.3% and 20.6%. The following rates were also calculated: complete response rate (CR): 2.9%; partial response rate (PR): 35.9%; stable disease rate (SD): 41.2%; overall response rate (OR): 34.6%; disease control rate (DCR): 76.7%; progressive disease: 23.1%; and grade III/IV adverse events (AEs): neutropenia 23.1%, febrile neutropenia 4.8%, thrombocytopenia 4.8%, anaemia 5.7%, fatigue 11.5%, nausea 9.1%, diarrhoea 10.1%, vomiting 5.7%, neuropathy 3.8%, and increased ALT 5.7%. In conclusion, modified FOLFIRINOX could provide comparative survival benefits with fewer adverse events compared to the conventional dosage.